Air Pollution and Solar Energy: Evidence from Wildfires - Seung Min Kim; Kenneth Gillingham (Center for Economic Studies and ifo Institute (CESifo), 2024)
There is strong evidence on the mortality and morbidity external costs of air pollution. This paper focuses on another source of air pollution externality: the loss in solar electricity generation from increased atmospheric opacity due to air pollution. We use data from residential rooftop solar panels and exploit quasi-random variation in air opacity from wildfire smoke and wind conditions to estimate that PM2.5 pollution reduced annual solar generation in California by over 450GWh, or 4% of total potential generation. This is equivalent to an annual externality of 177 per ton of PM2.5 emitted. Our findings suggest that there is a positive feedback from decarbonisation policies, where reduced dependence on fossil fuels improves air quality, leading to an even greater productivity of solar generation, further reducing emissions.
Keywords: Q48; 330; solar energy; air pollution; equity